Graig, Y - Llewelyn, Haf (Y Lolfa, 2010)
The novel is located in Y Graig, a typical Welsh farm facing a critical period as the young generation seeks to plough its own furrow. A tension-filled novel which creates a powerful and honest picture of modern day rural Wales. Intro – Yr Hen Ŵr – Llyr – Aled – Lilian – Alice – Yr Hen Ŵr – Llyr – Aled – Lilian – Alice – Yr Hen Ŵr – Llyr – Aled – Lilian – Alice – Yr Hen Ŵr – Llyr – Aled – Alice – Llyr – Yr Hen Ŵr.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books